Authorities in early modern law courts - Rossi, Guido (Law teacher) (Edinburgh studies in law ;, 2021)
Focusing deliberately on the impact of law courts on substantive law - and not on its systematisation by learned jurists - it studies similarities and differences in the development of the law across different jurisdictions. In doing so it evaluates whether and to what extent it is possible to consider this development as a unitary and truly European phenomenon. This collection re-evaluates current debates surrounding the development of civil law in the early modern period in the context of the grand narratives of European legal history and sets out to challenge current orthodox views about early modern civil law.